Radiation-induced basal cell carcinoma - Omid Zargari (Mattioli1885, 2015)
Background: The treatment of tinea capitis using radiotherapy was introduced at the beginning of the twentieth century. A variety of cancers including basal cell carcinoma (BCC) are seen years after this treatment. Objective: We sought to determine the clinical characteristics of BCCs among irradiated patients. Methods: The clinical records of all patients with BCC in a clinic in north of Iran were reviewed. Results: Of the 58 cases of BCC, 29 had positive history for radiotherapy in their childhood. Multiple BCCs were seen in 79.3% and 10.3% of patients with history and without history of radiotherapy, respectively. Conclusions: X-ray radiation is still a major etiologic factor in developing BCC in northern Iran. Patients with positive history for radiotherapy have higher rate of recurrence.